Analisis Total Productive Maintenance Pada Industri Percetakan - Farid Marhaban; Dwi Indra Prasetya; Fibi Eko Putra (DPPM Universitas Pelita Bangsa, 2022)
In the production process there is still a lot of damage suffered on the machine, one of which is the production target that was not achieved due to the defective product. In the production process, one of the machines in the printing industry is the HD Speed ​​Master’s machine which often has problems, the HD Speed ​​Master’s machine used in the production process serves as a paper printing machine. A common problem with this machine is the high frequency of damage, so that the printing paper suffers from defects such as blurred ink, skewed process results, torn paper and there are parts that are not printed so as to interfere with production process. The purpose of this study was to identify the effectiveness of HD Speed ​​Master’s machine using Overall Equipment Effectiveness (OEE) approach. Based on the analysis conducted on the HD Speed ​​Master’s machine, the result from the OEE calculation is 81%. Does not meet the company's standard of 85%. The low OEE value is due to the large amount of downtime that occurs in the machine, so the machine does not work effectively and efficiently. Keywords: Maintenance, downtime, Total Productive Maintenance, Overall Equipment Effectiveness